Prawa podstawowe w systemie konstytucyjnym Niemieckiej Republiki Demokratycznej - Malicka, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The German Democratic Republic, as a state of real socialism, guaranteed its citizens, in addition to classical individual fundamental rights, also collective rights. Their use was made conditional, depending on the fulﬁlment of obligations speciﬁed in the Constitution. In the GDR, there were no independent bodies and mechanisms to protect the rights of citizens. Constitutional system of fundamental rights was primarily serving the good of the community and the development of a modern socialist state.
Keywords: prawa podstawowe; konstytucja; socjalizm; prawa jednostki; prawa kolektywne; demokracja ludowa